Resilient Cities - Newman, Peter; Beatley, Tim; Boyer, Heather (Rizzoli, 2012)
Resilience is increasingly being used as a way to describe human activities that are smart, secure, and sustainable. They are smart in that they are able to adapt to the new technologies of the twenty-first century, secure in that they have built-in systems that enable them to respond to extreme events as well as being built to last, and sustainable in that they are part of the solution to the big questions of sustainability such as how to minimize our impact or adapt to climate change, prepare for peak oil, and protect biodiversity. Resilience thinking has been applied mostly to regions and natural resource management systems, but is increasingly being applied to cities.